Interpreting a Regional Knowledge Centre - Besenyei, Lajos (Theory, Methodology, Practice – Review of Business and Management, 2005)
The 21st century is the century of paradigm change, the century of the development of completely new structures, and of the rearrangement of the old ones. The exponential development trends reach points of breakthrough, and the earlier quantity accumulation of the changes turns into qualitative leaps. Contemporary times, the initial, very first period of which is our times, project the future image of a new society and economy, in which the material dimensions of products and services keep diminishing, the mass of knowledge accumulated in them keeps increasing, and the ratio of added value rises steadily. Large industrial centres look more and more like large research institutes, and the qualification level of the labour force used in the production of goods is steadily increasing. Their locations tend to get closer and closer to large university campuses, and all the features suggest a dramatic increase in the demand for knowledge. Knowledge centres come into being, and become more and more attractive for capital investors as well. In the 21st century it is the production, reproduction and distribution of knowledge that is worth investing in.